The Tale of Jamu : The Green Gold of Indonesia - Martha Tilaar (PT Gramedia Pustaka Utama, 2016)
The book takes you on a journey of Indonesian herbal medicine, jamu, throughout centuries from the engravings on the wall of Borobudur temple to the streets of Indonesian villages and cities carried by elegant jamu peddling ladies. This iconic heritage is nowadays featured at international hotels and malls as part of the modern trend in health and beauty care. The prominence of jamu is also apparent in modern spas that represent a current lifestyle. Dedicated by Dr. Martha Tilaar, an expert in cosmetics and beauty care who has an undying passion for jamu, this book reveals interesting aspects of the typical Indonesian herbal medicine.